The Malleability of Injunctive Norms Among College Students - Prince, Mark A. (2010)
Alcohol use among college students has been associated with injunctive norms, which refer to the perceived acceptability of excessive drinking, and descriptive norms, which refer to perceptions of actual drinking. The purpose of this study was to examine the effect of a brief injunctive norms manipulation on both injunctive and descriptive norms about drinking alcohol and to explore differences in the malleability of norms across referent groups, sex, and gender role. Participants were 265 undergraduates (43% male, 70% freshmen) who completed a web-based survey for course credit. A randomly selected half were exposed to a page of information-based feedback about typical student injunctive norms. Relative to the control condition, the manipulation produced lower injunctive and descriptive norms related to typical students’ drinking but no change in either type of norm related to close friends. Femininity was associated with less permissive normative beliefs about the acceptability of excessive drinking whereas masculinity was associated with elevated perceptions of peer drinking, but neither sex nor gender role moderated the manipulation effect. We conclude that perceptions of peer approval of drinking are malleable with a very brief information-based manipulation.